China’s Investments in Germany and the Impact of the COVID-19 Pandemic - Xinming Xia; Wan-Hsin Liu (Intereconomics)
Abstract This paper analyses how China’s investments in Germany have developed over time and the potential impact of the COVID-19 pandemic in this regard, based on four different datasets, including our own survey in mid-2020. Our analysis shows that Germany is currently one of the most attractive investment destinations for Chinese investors. Chinese state-owned enterprises have played an important role as investors in Germany — particularly in large-scale projects. The COVID-19 pandemic has had some negative but rather temporary effects on Chinese investments in Germany. Germany is expected to stay attractive to Chinese investors who seek to gain access to advanced technologies and know-how in the future.